2000
DOI: 10.2355/isijinternational.40.suppl_s194
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Substructures in Hot-deformed Ni-based Alloys: Simulation for Structure Evolution of Hot-worked Austenite in Low Carbon Steels

Abstract: The dislocation substructure in compressively deformed fcc 70Ni-30Fe and 67Ni-30Fe-3Ti alloys was investigated to understand or model microstructural evolution in austenite of low carbon steels during hot deformation. These Ni-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Almost homogeneous distribution of equiaxed and cellar arrays of dislocations are observed, which are very similar to those observed in cold-rolled fcc alloys 33) as well as hot-rolled Ni30%Fe. 34,35) The average cell diameter is approximately 0.4 mm. Although the misorientation angle between neighboring cells is mostly very small, some of the cell walls in the present experiment show large misorientation over 10°a s shown in Fig.…”
Section: Ni-30%fe Model Alloymentioning
confidence: 99%
“…Almost homogeneous distribution of equiaxed and cellar arrays of dislocations are observed, which are very similar to those observed in cold-rolled fcc alloys 33) as well as hot-rolled Ni30%Fe. 34,35) The average cell diameter is approximately 0.4 mm. Although the misorientation angle between neighboring cells is mostly very small, some of the cell walls in the present experiment show large misorientation over 10°a s shown in Fig.…”
Section: Ni-30%fe Model Alloymentioning
confidence: 99%
“…Entwisle 22) and Magee 23) reported that kinetics of isothermally formed martensite depends largely on the grain size when it is down to 20 mm, and Wang et al 14) thought that nucleus density required by an athermal nucleation mechanism could be achieved only when the dispersed austenite grain size is as small as 1 mm. Adachi et al 18) even presented experimental evidence that the sizes of dislocation cells produced by austenitic deformation above 800°C were around 1 mm. The prior austenite grain size ranges from 15 to 28 mm in our investigation, thus, it could be estimated that this critical size is at least less than 10 mm, most likely in the scale of a few micrometers or even smaller, since the prior austenite grain sizes of industrial TRIP steels are usually quite fine.…”
Section: Mechanism For Influence Of Intercritical Deformation On Bainmentioning
confidence: 99%
“…The ferrite nucleated to form parallel and closely spaced arrays within one prior austenite grain. By using the similar model alloy, Adatchi et al 18) made the more detailed observation that deformation substructure are microbands below 700°C whilst equiaxed dislocation cell structures above 800°C. All of these previous researches support that austenitic deformation may produce such deformation microstructures as microbands and dislocation cells.…”
Section: Mechanism For Influence Of Intercritical Deformation On Bainmentioning
confidence: 99%
“…[3][4][5] Also we simulated the effect of the gradual variation in orientation within an austenite grain, which developed during the process of deformation, on the orientation distribution characteristics of statically transformed ferrite, and compared the results of this simulation with the experimental observations. In this simulation, the K-S relationship between the deformed austenite and statically transformed ferrite was assumed.…”
Section: Introductionmentioning
confidence: 99%
“…9) Using this concept, the deformed grain structure of austenite has frequently been evaluated using Ni-30Fe alloy. [3][4][5] This alloy is known to have a stacking fault energy similar to that of low carbon austenite at high temperature.…”
mentioning
confidence: 99%